Capillary electrophoresis for glutathione and glutathione disulfide quantification to monitor oxidative stress by cadmium in Glycine max L. leaves - Felici, Carlos Emiliano (2011)
Antioxidant defense systems allow plants to develop a tolerance to contamination with cadmium (Cd). A rapid and accurate capillary electrophoresis (CE) method for the simultaneous determination of GSH and GSSG in Glycine max L. leaves was developed. The method was applied to monitor the oxidative stress after Cd adding. Soybean seeds were germinated under controlled conditions. On the 4th day were placed in hydroponic conditions, with Hoagland nutrient solution. On the 10th day were subjected to Cd poisoning (40 μM) for 4, 6, 24, 72 h and 6 days. To obtain extracts, 250 mg of leaves were homogenized under ice-cold conditions in HCl 0.5M. Homogenates were centrifuged for 10 min and the supernatants were analyzed. A Beckman P/ACE MDQ instrument equipped with a DAD and P/ACE System MDQ Software was used. Linear relationships were obtained between corrected peak areas and concentrations of the analytes. Detection was performed at 214 and 198 nm GSH and GSSG were baseline separated in less than 6 min, the corresponding migration times were 4.97 and 5.41 min, respectively. Along the time curve GSH levels were higher than in the respective controls, while GSSG was always lower. GSSG content in the analyzed samples was low and GSH content was high. However, both compounds could be separated and quantified fast and accurately without interference. The increased levels of GSH showed that the antioxidant mechanisms in the plant are working, defending it, and presenting a level of tolerance to Cd stress.